Cerebral white matter lesions in patients with cirrhosis – causative for hepatic encephalopathy or bystanders?. (21st January 2015) - Pflugrad, Henning; Bronzlik, Paul; Raab, Peter; Tryc, Anita B.; Goldbecker, Annemarie; Barg‐Hock, Hannelore; Strassburg, Christian P.; Ding, Xiao‐Qi; Lanfermann, Heinrich; Weissenborn, Karin
Abstract Background & Aims Focal white matter lesions mimicking microvascular lesions were connected to the development of hepatic encephalopathy (HE) in patients with cirrhosis. This study aims to assess the relationship between cerebrovascular risk factors and the prevalence and extent of these lesions in patients with cirrhosis, as well as their impact upon cognitive function. Methods 55 cirrhotic patients underwent neurological examination, psychometric testing and magnetic resonance imaging. T2‐weighted images were reviewed for white matter lesions by a neuroradiologist and a neurologist, independently. Patients were allocated into three groups: (i) no or <5, (ii) 6–15 and (iii) more than 15 lesions. Allocation was confirmed by a senior neuroradiologist blinded for the clinical data. The patient groups were compared concerning age, underlying liver disease, mortality, MELD Score, history of HE, treatment for HE, cerebrovascular risk factors and psychometric test results. Regression analysis was performed to identify risk factors for the presence and extent of white matter lesions. Results Patient groups 2 and 3 were older and showed worse results in the psychometric tests than group 1 (P < 0.05). Correlation analyses showed a significant relationship between the number of white matter lesions and the grade of HE (P < 0.001) and cognitive function (P < 0.05), but no interrelationship between the lesions and cerebrovascular risk factors or other factors tested. Conclusions Focal white matter lesions in patients with cirrhosis do not represent cerebrovascular small‐vessel disease but are related to the pathology of HE. Further studies are needed to clarify the mechanisms behind in detail.